Cognitive behaviour therapy for non-cardiac pain in the chest (COPIC): a multicentre randomized controlled trial with economic evaluation - Tyrer,PJ; Tyrer,H; Cooper,S; Barrett,B; Kings,S; Lazarevic,V; Bransby-Adams,K; Whittamore,K; Walker,G; McNulty,A; Donaldson,E; Midgley,L; et al. (BMC Psychology, 2015)
BackgroundMost patients with chest pain have nothing wrong with their cardiac function. Psychological forms of treatment for this condition are more likely to be successful than others.Methods/designA two-arm parallel controlled randomized trial of standard care versus a modified form of cognitive behaviour therapy for chest pain (CBT-CP) in patients who have attended emergency hospital services. Inclusion criteria include (i) emergency attendance more than once in the previous year with chest pain when no physical pathology has been found, (ii) aged between 16 and 75, (iii) signed consent to take part in the study. Exclusion criteria are (i) under current psychiatric care, (ii) those who have had new psychotropic drugs prescribed within the last two months, (iii) are receiving or about to receive a formal psychological treatment. Those satisfying these criteria will be randomized to 4–10 sessions of CBT-CP or to continue with standard care.Participants are randomized using a remote web-based system using permuted stacked blocks stratified by study centre. Assessment is carried out at baseline by researchers subsequently masked to allocation and at 6 months and 1 year after randomization. The primary outcome is the Health Anxiety Inventory score at 6 months, and secondary outcomes are generalised anxiety and depressive symptoms, the Lucock Health Anxiety Questionnaire adapted for chest pain, visual analogue scales for chest pain and discomfort (Inskip Scale), the Schedule for Evaluating Persistent Symptoms (SEPS), health related quality of life, social functioning and medical resource usage. Intention to treat analyses will be carried out with clinical and functioning data, and a cost-utility analysis will compare differences in total costs and differences in quality of life using QALYs derived from the EQ-5D. The data will also be linked to another parallel study in New Zealand where 126 patients with the same inclusion criteria have been treated in a similar